United Arab Emirates : 2013 Article IV Consultation. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2013)
This staff report on United Arab Emirates 2013 Article IV Consultation highlights economic policies and development. Against a backdrop of political stability, confidence has further increased, tourism has been firm, demand from expatriates from the broader region has increased, and capital inflows have strengthened amid high global liquidity. The real estate sector, which had been impaired since the 2009 crisis, has stabilized in Abu Dhabi and has started to recover in Dubai. Dubai aims to build on its early achievements in becoming a hub for retail and wholesale trade, as well as a major tourism and real estate investment destination for the wider region. It has announced plans for several new megaprojects in real estate and tourism.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet